Psykhe (Santiago) 2022
DOI: 10.7764/psykhe.2021.31721
|View full text |Cite
|
Sign up to set email alerts
|

Legitimidad, Justicia y Justificación de la Violencia Intergrupal entre Carabineros y Manifestantes en Chile

Abstract: ¿Por qué justifican las personas la violencia intergrupal ejercida entre la policía y manifestantes en protestas sociales? En este artículo se examinan las actitudes hacia la violencia perpetrada en Chile por Carabineros contra manifestantes y la violencia ejercida por manifestantes contra Carabineros en el marco del contexto post estallido social del 18 de octubre de 2019. Se evalúa el papel que juegan la percepción de injusticia en los procedimientos y el trato de Carabineros hacia manifestantes, la evaluaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
(70 reference statements)
1
7
0
3
Order By: Relevance
“…The threat posed by violent protests, therefore, could increase justification or qualification of human rights restrictions ( Metcalfe and Pickett, 2022 ). These results reaffirm the importance of within-country variation and subnational factors to understand political attitudes and human rights attitudes in particular ( Barton et al, 2017 ; Crow, 2017 ), and contribute to our understanding of when public opinion justifies police violence ( Jackson et al, 2013 ; Gerber and Jackson, 2017 ; Gerber et al, 2023 ). Other works could further explore the relationship between threats and support for human rights restrictions in the context of protest and civil unrest, which has usually emphasized other types of perceived threats ( McLaren, 2003 ; Barth et al, 2015 ; Abrams et al, 2017 ).…”
Section: Discussionsupporting
confidence: 65%
“…The threat posed by violent protests, therefore, could increase justification or qualification of human rights restrictions ( Metcalfe and Pickett, 2022 ). These results reaffirm the importance of within-country variation and subnational factors to understand political attitudes and human rights attitudes in particular ( Barton et al, 2017 ; Crow, 2017 ), and contribute to our understanding of when public opinion justifies police violence ( Jackson et al, 2013 ; Gerber and Jackson, 2017 ; Gerber et al, 2023 ). Other works could further explore the relationship between threats and support for human rights restrictions in the context of protest and civil unrest, which has usually emphasized other types of perceived threats ( McLaren, 2003 ; Barth et al, 2015 ; Abrams et al, 2017 ).…”
Section: Discussionsupporting
confidence: 65%
“…The attitudes of the citizenry towards the police constitute an increasingly relevant topic in public discourse, police agendas, and academic debates (Sargeant et al, 2018). The literature has evidenced how individuals' evaluations of the police influence their willingness to use violence as a means of promoting social change (Gerber et al, 2018(Gerber et al, , 2023, comply with laws (Hamm et al, 2017;Jackson & Bradford, 2019), cooperate with police directives (Jackson et al, 2012;Tyler, 2006), as well as their perceptions of police legitimacy (Murphy & Cherney, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This article aims to contribute to overcoming this gap in the literature, by presenting the results of two studies aimed to adapt and validate a Scale of Motivational Postures towards the Police in Spanish, by focusing on the Chilean context. The case of Chile is interesting, as the relationship between the citizenry and the police has been strained due to significant levels of police repression in citizen protests in recent years (Gerber et al, 2023), showing, at the same time, a great level of volatility. A vicious circle has emerged between police repression, negative attitudes of the citizenry towards the police, and violence as a response from the citizenry towards the police.…”
Section: Introductionmentioning
confidence: 99%
“…Collective actions are a key aspect towards social change ( Thomas and Louis, 2013 ). From student manifestations against tuition fees in Germany ( Tausch et al, 2011 ), to social protests in Armenia during the Velvet Revolution ( Burrows et al, 2022 ), the Egyptian revolution ( Sadowski et al, 2017 ), and the Chilean social outburst of 2019 ( Castro-Abril et al, 2021 ; Gerber et al, 2023 ) collective actions have occurred throughout history and all around the world. However, although collective actions are directed towards goals, they rarely achieve them right away ( Louis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental studies were carried out in Chile, which has been the scenario of many important social movements over the years, as illustrated by the social movement that brought Salvador Allende to power in 1970, the social movements against Pinochet’s dictatorship in the 80s, the student movements of 2006 and 2011 onwards, and more recently the social outburst of 2019 ( Chayinska et al, 2021 ; Cornejo et al, 2021 ; González et al, 2021 , 2022 ; Smith et al, 2021 ; Medel et al, 2022 ; Gerber et al, 2023 ). The studies reported here were carried out as part of a broader project addressing the social psychological consequences of participating in collective actions, using longitudinal data ( González et al, 2021 ), mixed methods with dyads of parents and children ( Cornejo et al, 2021 ; González et al, 2021 ), and, for the case of the studies presented here, experimental data.…”
Section: Introductionmentioning
confidence: 99%